Challenges of applying distance education in public schools from the point of view of school principals and teachers in Al Dakhiliyah Governorate, Sultanate of Oman - Al-kindi, Aflah Ahmed Sulaiman; Al-Dhuhli, Rabia AlMur Ali (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the challenges of applying distance education in public schools from the point of view of school principals and teachers in Al Dakhiliyah Governorate in the Sultanate of Oman. The researchers used the descriptive approach through a questionnaire consisting of four axes. These axes are concerned with challenges related to the administrative and financial aspects of the institution, challenges related to the student, challenges related to teaching and evaluating educational content and challenges related to teaching and administrative staff. After ensuring its validity and stability, it was distributed to a sample of (90) school principals, and (914) teachers in public schools in Al Dakhiliyah Governorate.The results revealed that the level of challenges applying distance education, as seen by school principals and teachers, came to a large extent on the four axes, and on the total degree, with an arithmetic average (3.94) for the total degree, and at a rate of (73.8%). In addition, the results found that there were no statistically significant differences between the average response of school principals and teachers to the challenges of applying distance education in government schools from their point of view due to the job variable, While there are statistically significant differences between the average response due to gender; In favor of the female category. The study came out with a set of recommendations that emphasize some of the proposals, and the re-legislation and regulations of student affairs to suit distance learning.
Keywords: challenges; application; distance education; school principals; Sultanate of Oman